Diversion Remains the Standard of Care for Modern Management of War-Related Rectal Injuries. Issue 7 (1st July 2014) - O'Donnell, Mary T.; Greer, Lauren T.; Nelson, Jeffery; Shriver, Craig; Vertrees, Amy
ABSTRACT: Introduction: Management of rectal injuries in war-injured patients has evolved over time. Methods: Retrospective review of records of patients sustaining war-related rectal injuries admitted to Walter Reed Army Medical Center from Iraq and Afghanistan. Results: From 2003 to 2011, 67 males ages 18 to 40 sustained rectal injuries after secondary blast (64%), gunshot (33%), motor vehicle crash (1%), or helicopter crash (1%). Injuries were extraperitoneal (72%), intraperitoneal (25%), or both (3%). Rectal abbreviated injury score mean was 3 ± 1. Surgical management included end colostomy (66%), loop colostomy (28%), and no diversion (4%). Distal washout (24%) and drain placement (33%) were performed. Colostomy closure occurred in 79% of patients at an average of 237 days after injury. Conclusions: Diversion is the preferred treatment of war-related rectal injuries. Loop colostomy is acceptable unless there is potential for evolving rectal injury. Routine use of presacral irrigation and drainage was not supported.